Identification of Escherichia coli ygaQ and rpmG as novel mitomycin C resistance factors implicated in DNA repair. Issue 1 (22nd January 2016) - Bolt, Edward L.; Jenkins, Tabitha; Russo, Valeria Moreira; Ahmed, Sharlene; Cavey, James; Cass, Simon D.
Abstract : A genome-wide protein expression screen in Escherichia coli has identified new mitomycin C resistance factors, genes ygaQ and rpmG . These were characterized, revealing that ygaQ encodes a new nuclease enzyme and that RpmG is likely be an "idiosyncratic ribosomal protein" with a role in DNA repair by MutM. Abstract : Using the ASKA (A CompleteS et of Escherichia coli K -12 ORFA rchive) library for genome-wide screening of E. coli proteins we identified that expression of ygaQ and rpmG promotes mitomycin C resistance (MMC R ). YgaQ mediated MMC R was independent of homologous recombination involving RecA or RuvABC, but required UvrD. YgaQ is an uncharacterized protein homologous with α-amylases that we identified to have nuclease activity directed to ssDNA of 5′ flaps. Nuclease activity was inactivated by mutation of two amino acid motifs, which also abolished MMC R . RpmG is frequently annotated as a bacterial ribosomal protein, although forms an operon with MutM glycosylase and a putative deubiquitinating (DUB) enzyme, YicR. RpmG associated MMC R was dependent on MutM. MMC R from RpmG resembles DNA repair phenotypes reported for 'idiosyncratic ribosomal proteins' in eukaryotes.